2015
DOI: 10.1371/journal.pone.0134696
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Maturation in Women with vs. without Polycystic Ovarian Syndrome: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo evaluate in vitro maturation (IVM) in sub-fertile women with polycystic ovarian syndrome (PCOS) undergoing in vitro fertilisation (IVF), by comparing outcomes with a control group of non-PCOS.Study designA search strategy was developed for PubMed and studies reporting rates of the following outcomes (live birth; clinical pregnancy; implantation; cycle cancellation; oocyte maturation; oocyte fertilization; miscarriage) between patients with PCOS, PCO and controls undergoing IVM were deemed eligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 38 publications
1
40
0
2
Order By: Relevance
“…The IVM technique has been used to preserve the fertility of women with malignancy, 3,30,38 to treat infertility of F I G U R E 3 Evaluation of the effects of MSC-CM supplementation on oocyte in vitro maturation. Representative images (A) and quantitative data (B) for intracellular glutathione (GSH) levels, as cytoplasmic maturation marker, in the in vitro matured oocytes from PCOS and normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…The IVM technique has been used to preserve the fertility of women with malignancy, 3,30,38 to treat infertility of F I G U R E 3 Evaluation of the effects of MSC-CM supplementation on oocyte in vitro maturation. Representative images (A) and quantitative data (B) for intracellular glutathione (GSH) levels, as cytoplasmic maturation marker, in the in vitro matured oocytes from PCOS and normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…compared clinic outcomes of 2632 PCOS women with 28523 non-PCOS women undergoing ARTs, and found that there are higher number of available embryo and clinic pregnancy rate in PCOS women than in non-PCOS6. A meta-analysis showed that birth and implantation rates were higher in PCOS patients than in controls using in vitro maturation7. Heijnen et al .…”
mentioning
confidence: 99%
“…The major underlying reason for this reduction is the fact that testicular sperms of azoospermic men are more likely to have centriolar and genetic defects. Therefore, the ability of the sperms to fertilize the oocytes and induce the formation and development of a viable zygote is impaired (9,20,21).…”
Section: Discussionmentioning
confidence: 99%